Kaempferol‐3‐rhamnoside overaccumulation in flavonoid 3′‐hydroxylase tt7 mutants compromises seed coat outer integument differentiation and seed longevity. Issue 4 (12th March 2023) - Niñoles, Regina; Arjona, Paloma; Azad, Sepideh M.; Hashim, Aseel; Casañ, Jose; Bueso, Eduardo; Serrano, Ramón; Espinosa, Ana; Molina, Isabel; Gadea, Jose
Summary: Seeds slowly accumulate damage during storage, which ultimately results in germination failure. The seed coat protects the embryo from the external environment, and its composition is critical for seed longevity. Flavonols accumulate in the outer integument. The link between flavonol composition and outer integument development has not been explored. Genetic, molecular and ultrastructural assays on loss‐of‐function mutants of the flavonoid biosynthesis pathway were used to study the effect of altered flavonoid composition on seed coat development and seed longevity. Controlled deterioration assays indicate that loss of function of the flavonoid 3′ hydroxylase gene TT7 dramatically affects seed longevity and seed coat development. Outer integument differentiation is compromised from 9 d after pollination in tt7 developing seeds, resulting in a defective suberin layer and incomplete degradation of seed coat starch. These distinctive phenotypes are not shared by other mutants showing abnormal flavonoid composition. Genetic analysis indicates that overaccumulation of kaempferol‐3‐rhamnoside is mainly responsible for the observed phenotypes. Expression profiling suggests that multiple cellular processes are altered in the tt7 mutant. Overaccumulation of kaempferol‐3‐rhamnoside in the seed coat compromises normal seed coat development. This observation positions TRANSPARENT TESTA 7 and the UGT78D1 glycosyltransferase, catalysing flavonol 3‐O‐rhamnosylation, as essential players in the modulation of seed longevity.